Winter stress resistance of apple tree under the conditions of Krasnodar Territory - G. K. Kiseleva; E. V. Ulyanovskaya; T. V. Skhalyakho; A. V. Karavaeva (Труды по прикладной ботанике, генетике и селекции)
Background. Physiological and biochemical research on winter stress resistance of apple-tree cultivars of different ecogeographic origin under global warming is important for identifying the most adaptable genotypes for use in breeding practice. Such resistance is associated with the content of carbohydrates and anthocyanins, and the activity of peroxidase.Materials and methods. Two winter apple-tree cultivars developed at the North Caucasian Federal Scientific Center of Horticulture, Viticulture, Wine making (NCFSCHVW) and 3 foreign winter cultivars were studied using conventional physiological and biochemical methods.Results and discussion. The apple-tree cultivars ‘Orfey’ and ‘Prikubanskoye’ bred at the NCFSCHVW, when compared with foreign cvs. ‘Enterprise’, ‘Florina’ and ‘Ligol’, demonstrated higher contents of total water (by 2.5 %), starch (by 9.5 mg/g) and water-soluble sugars (by 19.3 mg/g) in shoots during the winter period. In the process of wintering, the anthocyanin content increased 2.9–4.3 times in the domestic cultivars, and 2.4–2.8 times in foreign ones. No regularities were found between the level of total peroxidase activity and winter hardiness of the studied apple cultivars.Conclusion. Cvs. ‘Orfey’ and ‘Prikubanskoye’ showed increased adaptability to the winter conditions in the unstable climate of Southern Russia, and can be recommended for cultivation in Krasnodar Territory and use in breeding practice.